Notoginsenoside R1 Regulates Ischemic Myocardial Lipid Metabolism by Activating the AKT/mTOR Signaling Pathway - Wei Lei; Wei Lei; Wei Lei; Yiqi Yan; Yiqi Yan; Yiqi Yan; Yaolei Ma; Yaolei Ma; Yaolei Ma; Min Jiang; Boli Zhang; Boli Zhang; et al. (Frontiers Media S.A., 2022)
Ischemic heart diseases are responsible for more than one-third of all deaths worldwide. Radix notoginseng is widely used to treat ischemic heart disease in China and other Asian countries, and notoginsenoside R1 (NGR1) is its characteristic and large-amount ingredient. However, the potential molecular mechanisms of NGR1 in improving ischemic heart diseases are unclear. In this study, we combined pharmacological evaluation with network pharmacology, myocardial proteomics, and conventional molecular dynamics (MD) simulation to explore the cardio-protection mechanisms of NGR1. Our results revealed that NGR1 improved the echocardiographic, tissue pathological, and serum biochemical perturbations in myocardial ischemic rats. The network pharmacology studies indicated that NGR1 mainly regulated smooth muscle cell proliferation, vasculature development, and lipid metabolism signaling, especially in the PI3K/AKT pathway. Myocardial proteomics revealed that the function of NGR1 was focused on regulating metabolic and energy supply processes. The research combined reverse-docked targets with differential proteins and demonstrated that NGR1 modulated lipid metabolism in ischemic myocardia by interacting with mTOR and AKT. Conventional MD simulation was applied to investigate the influence of NGR1 on the structural stabilization of the mTOR and AKT complex. The results suggested that NGR1 can strengthen the affinity stabilization of mTOR and AKT. Our study first revealed that NGR1 enhanced the affinity stabilization of mTOR and AKT, thus promoting the activation of the AKT/mTOR pathway and improving lipid metabolic abnormity in myocardial ischemic rats.